Sit at my right hand : the Chronicler’s portrait of the tribe of Benjamin in the social context of Yehud - Giffone, Benjamin D. (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.